An evaluation method for interface adhesion of water-based traffic marking paint considering road surface structure and existing marking type

CN122961896APending Publication Date: 2026-10-23DALIAN MARITIME UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611312599.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]为解决现有方法未考虑沥青路面表面构造深度差异、未区分旧热熔标线损坏类型差异、评价维度单一、缺乏多尺度系统评价的问题,本发明提供了一种考虑路表面构造和既有标线类型的水性交通标线涂料界面黏附性评价方法,该方案构建了“微观(表面能/接触角)→细观(粗糙度/机械锁合)→宏观(拉拔/剪切/冻融强度)”多尺度黏附性评价方法,同时提出了多指标加权综合评分模型与黏附性等级划分标准(优/良/中/差四级)

Benefits of technology

本发明公开了一种考虑路表面构造和既有标线类型的水性交通标线涂料界面黏附性评价方法,该评价方法涵盖辽宁省典型沥青混合料类型(AC-13、SMA-13、OGFC-13)及旧热熔标线五种典型损坏类型,评价结果更贴合工程实际;同时该评价方法从微观(表面能、接触角)→细观(粗糙度、机械锁合)→宏观(拉拔/剪切/冻融强度)建立了系统评价体系,能够揭示界面黏结失效机理;此外,该评价方法包含7项核心指标,克服了单一指标评价的局限性,评价维度多元化;该方案提出黏附性等级划分标准,为旧标线修复方案的制定提供依据。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122961896A_ABST
    Figure CN122961896A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of traffic engineering material performance test and evaluation, and specifically discloses a water-based traffic marking paint interface adhesion evaluation method considering road surface structure and existing marking type. The evaluation method covers different surface structure depth asphalt mixture (AC-13, SMA-13, OGFC-13) and five kinds of damaged type old hot melt marking base material system; a systematic evaluation system is established from "micro (surface energy / contact angle) -> meso (roughness / mechanical interlocking) -> macro (pulling / shearing / freeze-thaw strength)", the interface bonding failure mechanism is revealed, and a set of multi-index weighted comprehensive scoring model and adhesion grade division standard (four levels of excellent / good / medium / poor) are provided, which can overcome the limitation of single index, and the evaluation result is more in line with the actual engineering demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of performance testing and evaluation technology of traffic engineering materials, and specifically relates to a method for evaluating the interfacial adhesion of water-based traffic marking paint that takes into account road surface structure and existing marking types. Background Technology

[0002] Water-based traffic marking paint uses water as a dispersion medium and has extremely low VOC content, gradually replacing traditional hot-melt paints. However, water-based paints have high surface tension, making it difficult to effectively wet and spread on asphalt pavements (which have low surface energy) and old hot-melt marking surfaces, resulting in insufficient adhesion and easy detachment of the markings.

[0003] Currently, the main methods for evaluating interfacial adhesion are the pull-out method (GB / T 5210) and the cross-cut method (GB / T 9286). However, these methods have the following prominent problems: First, they use a uniform substrate (steel plate or glass plate) for testing, failing to consider the influence of differences in the surface texture depth (0.3-1.5mm) of asphalt pavement on adhesion, resulting in significant differences in adhesion performance between pavement surfaces of different gradations (AC, SMA, OGFC); second, they fail to distinguish the differences in surface condition of different damage types of old hot-melt markings (wear and fading, cracking, peeling, blistering, and contamination); third, the single pull-out strength index is insufficient to comprehensively reflect the failure behavior of the interface under multiple stress modes such as shear and peeling; and fourth, they lack correlation analysis between microscopic interfacial mechanisms and macroscopic mechanical properties, making it impossible to reveal the bonding failure mechanism.

[0004] CN 112985973A discloses an evaluation index and method for the adhesion performance of road marking paint and glass beads. This scheme uses a paint film abrasion tester as the testing equipment to conduct abrasion tests on the samples, and evaluates the adhesion performance of the surface-applied glass beads by the mass loss of the glass beads before and after the test. This scheme mainly evaluates the adhesion performance between road marking paint and surface-applied glass beads, but does not disclose a testing and evaluation method for the interfacial adhesion performance between water-based traffic marking paint and asphalt pavement or existing hot-melt road marking substrate. It does not consider the influence of road surface structure and the damage state of existing markings on the coating-substrate interfacial adhesion performance, thus failing to reflect the adhesion and failure behavior between water-based road marking coatings and different substrates under actual road recoating conditions, and cannot achieve a multi-scale comprehensive evaluation of the coating-substrate interfacial adhesion performance.

[0005] CN 113804590A discloses a test method for the adhesion of road marking paint based on surface energy theory. The method includes the following steps: (1) Selecting three solutions with known surface energy parameters as probe solutions, and measuring the contact angles formed between the droplets of the three solutions and the surfaces of the road marking paint and asphalt mixture; (2) Substituting the contact angle measurement results into the Young's equation to calculate the surface energy of the paint and the surface energy parameters of the asphalt mixture; (3) Calculating the adhesion work between the paint and asphalt mixture interface using the measured surface energy component values ​​of the paint and the mixture. This technical solution is based on the theory of surface free energy and takes an adhesive approach. It uses contact angle to determine the surface parameters of coatings and asphalt mixtures. This solution mainly evaluates interfacial adhesion from a microscopic thermodynamic level based on surface energy and theoretical adhesion work. However, it does not disclose the classification and evaluation of actual road surface texture depth and different damage states of existing old hot-melt markings as substrate characteristics. It also does not establish a multi-scale evaluation system that combines surface roughness, mechanical interlocking, tensile strength, shear strength, post-freeze-thaw strength retention, and interfacial failure modes. As a result, the evaluation dimensions are relatively singular and it is difficult to fully reflect the actual interfacial bonding and durability failure behavior under complex road surface conditions. It is not suitable for the comprehensive evaluation of the interfacial compatibility of existing markings repainting and water-based marking coatings under different road surface texture conditions. It cannot meet the needs of comprehensive classification of interfacial adhesion performance and substrate compatibility determination in actual engineering. Summary of the Invention

[0006] To address the problems of existing methods failing to consider differences in the surface texture depth of asphalt pavements, failing to distinguish the differences in damage types of old hot-melt road markings, having a single evaluation dimension, and lacking multi-scale systematic evaluation, this invention provides a method for evaluating the interfacial adhesion of water-based traffic marking paints that considers road surface texture and existing marking types. This scheme constructs a multi-scale adhesion evaluation method of "microscopic (surface energy / contact angle) → mesoscopic (roughness / mechanical interlocking) → macroscopic (pull-out / shear / freeze-thaw strength)," and proposes a multi-index weighted comprehensive scoring model and an adhesion level classification standard (four levels: excellent / good / medium / poor).

[0007] To solve the above-mentioned technical problems, the present invention proposes the following technical solution: A method for evaluating the interfacial adhesion of water-based traffic marking paints, taking into account road surface texture and existing marking types, includes the following steps: Step 1, Substrate preparation: Prepare asphalt specimens with different structural depths, and collect old hot-melt marking samples with different damage types; Step 2, Surface Characterization: The texture depth was determined by the sand-spreading method, the surface roughness was obtained by three-dimensional laser scanning, and the surface energy was determined by the contact angle method. Step 3, Wetting test: The static contact angle of the water-based coating on the surface of each substrate is measured using an optical contact angle meter to evaluate the wetting and spreading ability. Step 4, Adhesion strength test: After applying a 0.6 mm thick water-based coating and curing for 7 days, test the pull-out strength, shear strength, and pull-out strength retention rate after freeze-thaw cycles according to GB / T 5210. Step 5, Failure Mode Analysis: Observe the failure interface and calculate the area ratio of the failure region to determine whether it is adhesion failure, cohesive failure or mixed failure. Step 6, Multi-scale comprehensive evaluation: Establish a three-level index system of micro (surface energy matching degree, static contact angle), meso (surface roughness Ra, micro mechanical locking coefficient), and macro (drawing strength, shear strength, and post-freeze-thaw drawing strength retention rate), weighted comprehensive score, and classify adhesion level (Level I Excellent / Level II Good / Level III Medium / Level IV Poor).

[0008] Surface energy matching degree Δγ: unit mJ / m 2 Microscopically, the thermodynamic possibility of spontaneous spreading of coatings on the substrate surface is determined, which is a prerequisite for interfacial adhesion to occur. Referring to Young's equation and Dupré's work of adhesion theory, when the surface energy of the coating is close to that of the substrate, the interfacial wetting is sufficient and the molecular-level contact area is large. This index plays a fundamental role in adhesion, A1=100×[1 [(Δγ / 10)], the smaller Δγ is, the higher the matching degree (Δγ is 1~10), and the weight W1=0.15.

[0009] Static contact angle θ: unit degree (°), microscopic. A contact angle less than 90° is the macroscopic criterion for wetting; the smaller the contact angle, the better the spreading. However, this index is affected by external factors such as substrate surface roughness and testing environment, resulting in large fluctuations in testing. Therefore, its weight is slightly lower than that of surface energy matching degree. A2=100×[1 [(θ / 180)], the smaller θ is, the better the wettability (θ is 0~180), weight W2=0.10.

[0010] Surface roughness Ra: In microscopic terms, moderate surface roughness is beneficial for microscopic mechanical bonding. However, when the roughness is too large, the coating is difficult to fully penetrate into the bottom of the valley, instead forming air entrainment and weakening the actual bonding area. This index has a non-monotonic relationship with adhesion, so its weight should not be too high; A3=100×[1 (Ra0 Ra 2 ) / Ra0 2 Ra0 is the reference roughness of each substrate (take the measured value of AC-13 as 18.3μm, and calculate Ra=Ra0 when Ra exceeds the reference value). Ra is 0~100, and the weight W3=0.10.

[0011] Microscopic mechanical interlocking coefficient C: At a microscopic level, it reflects the coating's ability to penetrate and fill the micropores on the substrate surface, directly determining the mechanical anchoring effect after curing. This index is obtained through SEM image analysis, but the representativeness of the image analysis area is limited, and the test error is relatively large. The weight is moderate, A4=C×100, C=coating penetration depth / substrate surface pore depth. The larger C is, the more sufficient the mechanical anchoring. C is 0~1; weight W4=0.10.

[0012] Pull-out strength σ: Unit MPa, macroscopic, the most direct and commonly used mechanical indicator for measuring interfacial adhesion, reflecting the coating's ability to resist interfacial peeling under normal stress. The test method follows a mature standard (GB / T 5210), with good data stability and high engineering acceptance. A5 = 100 × σ / 5, where a larger σ indicates stronger interfacial normal adhesion (σ ranges from 0 to 5); weight W5 = 0.20.

[0013] Shear strength τ: Unit MPa, macroscopic. In actual service, traffic markings mainly bear the horizontal shear force of vehicle tires, and shear strength is closer to the actual stress mode. However, shear strength testing is slightly affected by the variability of loading method and specimen preparation, so its weight is slightly lower than that of tensile strength. A6 = 100 × τ / 5, the larger τ is, the stronger the interfacial shear resistance (τ is 0~5); weight W6 = 0.15.

[0014] Freeze-thaw pull-out strength retention rate: This macroscopic indicator best reflects the long-term durability of coatings under harsh environments and is directly related to the frequent freeze-thaw cycles in Liaoning Province during winter. A retention rate that is too low renders even high initial strength meaningless in practical engineering applications. Its weight is tied with pull-out strength for the highest value. A7 = R, R = (freeze-thaw pull-out strength / initial pull-out strength) × 100%. The larger R is, the better the freeze-thaw durability (R ranges from 0 to 100%). Weight W7 = 0.20.

[0015] The engineering meaning of the comprehensive score S is: the comprehensive score of interfacial adhesion, with a maximum score of 100 points. The higher the score, the better the interfacial adhesion performance of the water-based coating on the substrate surface.

[0016] Based on the above technical solution, the raw material for the asphalt specimen in step 1 is selected from at least one of AC-13, SMA-13, and OGFC-13, and the texture depth is 0.4~1.5mm. In step 1, the old hot-melt marking samples include five types of damage: wear and fading, cracking, peeling and flaking, blistering and bulging, and contamination.

[0017] Based on the above technical solution, the pretreatment of the asphalt specimens in step 1 is as follows: use high-pressure air to blow away surface dust and loose particles, wipe the surface with anhydrous ethanol if necessary and let it dry, and place it under standard conditions of temperature 23±2℃ and relative humidity 50±5% for more than 24 hours for later use. The pretreatment of old hot-melt marking samples in step 1 is as follows: use high-pressure air to blow away surface dust and loose particles. For samples with contamination, use a damp cloth to gently wipe away obvious dirt on the surface (without changing the basic surface condition of the marking). Place the samples under standard conditions and let them stand for more than 24 hours for later use.

[0018] Based on the above technical solution, the freeze-thaw cycle conditions in step 4 are: freezing at -20℃ for 16 hours and then holding at 20℃ for 8 hours.

[0019] Based on the above technical solution, the failure mode analysis in step 5 is as follows: After the adhesion strength test is completed, retain and observe the two corresponding damaged surfaces. Without wiping or cleaning the residue on the damaged surfaces, take pictures in a way that is perpendicular to the damaged surfaces, and divide the failure area according to the location of the damage, the cross-sectional morphology and the material residue. When the damage mainly occurs at the interface between the water-based traffic marking coating and the asphalt mixture substrate or the existing old hot-melt marking substrate, and a large area of ​​the substrate surface is exposed, and there is no obvious tearing of the coating, old marking or asphalt mixture, it is judged as an adhesion failure. When the interface between the water-based coating and the substrate remains bonded, but the failure occurs inside the water-based coating, inside the old hot-melt marking, or inside the asphalt mixture, and corresponding material residue, tearing, aggregate pull-out, or mortar peeling can be observed on both damaged surfaces, it is judged as cohesive failure and noted as coating cohesive failure or substrate cohesive failure. When the same failure surface contains both an interface separation area where the substrate is exposed and an area where the coating or substrate is torn, it is determined to be a mixed failure.

[0020] Based on the above technical solution, image analysis method is used to calculate the area ratio of different failure areas; when the area of ​​interface adhesion failure accounts for no less than 80% of the effective damage area, it is judged as adhesion failure; when the sum of the areas of coating and substrate cohesive failure is no less than 80%, it is judged as cohesive failure; and other cases are judged as mixed failure. For the case where the existing old hot melt markings are completely separated from the asphalt pavement, it is recorded separately as the secondary interface failure of old hot melt markings-asphalt pavement.

[0021] Based on the above technical solution, the surface energy matching score is calculated as follows: A1 × weight W1 = 100 × [1 [(Δγ / 10)]×0.15, where Δγ is 1~10; The calculation of the static contact angle score is as follows: A2 × weight W2 = 100 × [1 [(θ / 180)]×0.10, where θ is 0~180; The surface roughness Ra score is calculated as follows: A3 × weight W3 = 100 × [1 (Ra0 Ra2 ) / Ra0 2 ]×0.10, Ra reference value is 0~100; when Ra exceeds the reference value, it is calculated as Ra=Ra0; The specific calculation of the micromechanical locking coefficient C is as follows: A4 × weight W4 = C × 100 × 0.10, where C is 0~1; The specific calculation of the tensile strength σ is as follows: A5 × weight W5 = 0.2 × 100 × σ / 5, where σ is 0~5; The specific calculation of the shear strength τ is as follows: A6 × weight W6 = 100 × τ / 5 × 0.15, where τ is 0~5; The score for the retention rate of pull-out strength after freeze-thaw is calculated as follows: A7 × weight W7 = R × 0.20, R = (pull-out strength after freeze-thaw / initial pull-out strength) × 100%, where R is 0~100%.

[0022] Based on the above technical solution, the formula for calculating the weighted comprehensive score S in step 6 is: S = A1 × 0.15 + A2 × 0.10 + A3 × 0.10 + A4 × 0.10 + A5 × 0.20 + A6 × 0.15 + A7 × 0.20.

[0023] Based on the above technical solution, when the comprehensive score S≥85 points, it indicates excellent interfacial adhesion and durability; at least 5 of the 7 indicators must reach 85 points or above (such as tensile strength ≥2.0MPa, shear strength ≥2.0MPa, freeze-thaw retention rate ≥70%), proving that the coating has excellent comprehensive performance on the substrate and belongs to the adhesion grade I (excellent). When 70 points ≤ comprehensive score S < 85 points, it indicates that the interface bonding performance is good and meets general usage requirements; when all indicators are not lower than 60 points (pass line) and at least 3 indicators reach 80 points or above, it indicates that there are no significant shortcomings, the overall performance meets the standards, and the adhesion level is Grade II (good). When 60 points ≤ comprehensive score S < 70 points, it indicates that the interfacial adhesion performance is average and requires formulation optimization or substrate pretreatment; if one or two indicators are below 60 points (such as low freeze-thaw retention rate or low pull-out strength), it indicates that there are obvious shortcomings that need to be improved, and the adhesion level is Class III (medium). When the comprehensive score S < 60 points, it indicates poor interfacial adhesion performance and direct use is not recommended; if multiple indicators are below 60 points or any one is below 40 points (such as tensile strength < 0.8MPa), it indicates that the substrate does not meet the engineering application conditions and belongs to the adhesion grade IV (poor).

[0024] Note: The classification of 85, 70, and 60 refers to the engineering practice in GB / T 5210 adhesion grade evaluation standard that a pull-out strength of ≥1.5MPa is considered qualified, as well as the minimum comprehensive performance requirements for water-based coatings to serve for more than 3 years in actual road marking applications.

[0025] Beneficial effects This invention discloses a method for evaluating the interfacial adhesion of water-based traffic marking paint, taking into account road surface structure and existing marking types. This method covers five typical damage types of old hot-melt markings in Liaoning Province, including typical asphalt mixture types (AC-13, SMA-13, OGFC-13), resulting in evaluation results that better reflect engineering realities. Furthermore, this method establishes a systematic evaluation framework from microscopic (surface energy, contact angle) to mesoscopic (roughness, mechanical interlocking) to macroscopic (pull-out / shear / freeze-thaw strength), revealing the interfacial adhesion failure mechanism. In addition, this method includes seven core indicators, overcoming the limitations of single-indicator evaluation and providing diversified evaluation dimensions. The scheme proposes an adhesion level classification standard, providing a basis for the formulation of old marking repair schemes. Attached Figure Description

[0026] Figure 1 Flowchart of the method for evaluating the interfacial adhesion of water-based traffic marking paint; Figure 2 This is a diagram illustrating the architecture of a multi-scale comprehensive evaluation index system. Detailed Implementation

[0027] To make the objectives and technical solutions of this invention clearer, the following embodiments are provided for further explanation. However, the scope of protection of this invention is not limited to these embodiments; the embodiments are merely for illustrative purposes. Those skilled in the art should understand that any changes or equivalent substitutions that do not depart from the concept of this invention are included within the scope of protection of this invention.

[0028] Unless otherwise specified, all reagents and raw materials used in this invention are obtained through purchase.

[0029] Example 1 This embodiment uses AC-13 and SMA-13 ​​asphalt mixture base materials, intact old road markings (W0), and old road markings of the wear and discoloration type (W1), cracked type (W2), and peeling type (W3) as examples for illustration: (1) Substrate preparation: AC-13 and SMA-13 ​​rut slabs were formed by wheel rolling, with structural depths of 0.52 mm and 1.05 mm respectively (the structural depth was determined by sand spreading method); old road marking samples with a size ≥200 mm × 200 mm were collected (five types of damage were collected simultaneously: wear and fading type, cracking type, peeling and flaking type, blistering type, and contamination covering type of old hot melt road marking samples). Asphalt mixture substrate specimens: Use high-pressure air to blow away surface dust and loose particles. If necessary, wipe the surface with anhydrous ethanol and let it dry. Place it under standard conditions of 23±2℃ and 50±5% relative humidity for more than 24 hours for later use.

[0030] Old hot-melt marking sample: Use high-pressure air to blow away surface dust and loose particles. For samples with contaminated coverage, use a damp cloth to gently wipe away obvious dirt on the surface (without changing the basic surface condition of the marking). Place it under standard conditions and let it stand for more than 24 hours for later use.

[0031] The formulation of the water-based coating is as follows: 40 parts of bio-based water-based polyurethane emulsion, 0.4 parts of silane coupling agent KH-550 (1% of the emulsion mass), 18 parts of water-based acrylic copolymer emulsion, 6 parts of nano silica, 10 parts of nano titanium dioxide, 15 parts of titanium dioxide, 10 parts of heavy calcium carbonate, 1.0 part of bio-based dispersant, 0.5 parts of bio-based defoamer, 2.0 parts of film-forming aid, 1.0 part of thickener, and 20 parts of deionized water.

[0032] (2) Surface property characterization: Surface roughness (Ra) was obtained by three-dimensional laser scanning, and surface energy was measured by the contact angle method; the AC-13 substrate had Ra=18.3μm and surface energy of 32.5mJ / m. 2 The SMA-13 ​​substrate has a Ra value of 32.5 μm and a surface energy of 34.2 mJ / m². 2 The surface energy of the old road markings is 25.8 mJ / m. 2 .

[0033] (3) Wetting test: The static contact angle of the water-based coating on each substrate surface was tested using an optical contact angle meter to evaluate the wetting and spreading ability. The contact angles of the water-based coating on AC-13, SMA-13, W0, W1, W2 and W3 were 52.3°, 48.7°, 67.5°, 61.2°, 68.9° and 70.3°, respectively.

[0034] (4) Adhesion strength test: After applying water-based coating (thickness 0.6 mm, curing for 7 days), the pull-out strength (GB / T5210), shear strength, and pull-out strength retention rate after freeze-thaw cycles (freezing at -20℃ for 16 h, and then keeping warm at 20℃ for 8 h) were tested; the pull-out strengths of AC-13, SMA-13, W0, W1, W2, and W3 were 1.85 MPa, 2.12 MPa, 1.12 MPa, 1.38 MPa, 1.05 MPa, and 0.95 MPa, respectively; the retention rates after 20 freeze-thaw cycles were 68.3%, 72.5%, not tested, 58.6%, not tested, and not tested, respectively.

[0035] (5) Failure Mode: After the adhesion strength test is completed, retain and observe the two corresponding damaged surfaces. Take photos perpendicular to the damaged surfaces without wiping or cleaning the residue. Divide the failure areas according to the location of the damage, the cross-sectional morphology, and the material residue. Use image analysis to calculate the area ratio of different failure areas. When the area of ​​interface adhesion failure accounts for no less than 80% of the effective damage area, it is judged as adhesion failure. When the sum of the areas of coating and substrate cohesive failure is no less than 80%, it is judged as cohesive failure. Other cases are judged as mixed failure. For cases where the existing old hot-melt markings are completely separated from the asphalt pavement, record them separately as secondary interface failure of old hot-melt markings-asphalt pavement.

[0036] When the damage mainly occurs at the interface between the water-based traffic marking coating and the asphalt mixture substrate or the existing old hot-melt marking substrate, and a large area of ​​the substrate surface is exposed without obvious tearing of the coating, old marking or asphalt mixture, it is judged as an adhesion failure.

[0037] When the interface between the water-based coating and the substrate remains bonded, but the damage occurs inside the water-based coating, inside the old hot-melt marking, or inside the asphalt mixture, and corresponding material residue, tearing, aggregate pull-out, or mortar peeling can be observed on both damaged surfaces, it is judged as cohesive failure and noted as coating cohesive failure or substrate cohesive failure.

[0038] When the same failure surface contains both an interface separation area where the substrate is exposed and an area where the coating or substrate is torn, it is determined to be a mixed failure.

[0039] After the adhesion strength test was completed, the two corresponding damaged surfaces were preserved and observed. Without wiping or cleaning any residue from the damaged surfaces, photographs were taken perpendicular to the damaged surfaces. Failure areas were then delineated based on the location of the damage, the cross-sectional morphology, and the amount of material residue. Image analysis methods were used to calculate the area proportion of different failure areas. The specific area proportions of the failure areas are shown in Table 1.

[0040] Table 1. Percentage of Failed Area

[0041] According to Table 1, in the AC-13 failure interface, the area of ​​adhesive failure accounts for approximately 35%, and the area of ​​cohesive failure accounts for approximately 65%, thus it is determined to be a mixed failure. In the SMA-13 ​​failure interface, the area of ​​adhesive failure accounts for approximately 30%, and the area of ​​cohesive failure accounts for approximately 70%, thus it is determined to be a mixed failure. In the failure interfaces of the old markings W0, W1, W2, and W3, the areas of adhesive failure account for approximately 85%, 70%, 90%, and 95%, respectively, and all are determined to be adhesive failures.

[0042] (6) Comprehensive evaluation: According to the comprehensive scoring formula S=A1×W1+A2×W2+A3×W3+A4×W4+A5×W5+A6×W6+A7×W7=A1×0.15+A2×0.10+A3×0.10+A4×0.10+A5×0.20+A6×0.15+A7×0.20, the comprehensive score of AC-13 is 77.2 points (Level II), SMA-13 ​​is 82.5 points (Level II), W1 is 70.5 points (Level II), W2 is 60.3 points (Level III), and W3 is 58.6 points (Level IV). The flowchart of the specific evaluation method for the interface adhesion of water-based traffic marking paint can be found in [link to flowchart]. Figure 1 The comprehensive evaluation index system architecture diagram is shown below. Figure 2 .

[0043] Example 2 In this embodiment, AC-13, SMA-13, and OGFC-13 were used as substrates to verify the effect of formulation optimization on improving interfacial adhesion performance.

[0044] (1) Substrate preparation: AC-13, SMA-13 ​​and OGFC-13 rutted plates were formed by wheel rolling method, with structural depths of 0.52 mm, 1.05 mm and 1.32 mm respectively (structural depth was determined by sand spreading method).

[0045] (2) Coating formulation: The optimized waterborne coating formulation is as follows: 50 parts of bio-based waterborne polyurethane emulsion, 0.5 parts of silane coupling agent KH-550 (1% of the emulsion mass), 18 parts of waterborne acrylic copolymer emulsion, 6 parts of nano silica, 10 parts of nano titanium dioxide, 15 parts of titanium dioxide, 10 parts of heavy calcium carbonate, 1.0 part of bio-based dispersant, 0.5 parts of bio-based defoamer, 2.0 parts of film-forming aid, 1.0 part of thickener, and 20 parts of deionized water.

[0046] The waterborne polyurethane emulsion was increased from 40 parts to 50 parts + 1% coupling agent, and the remaining testing procedures were the same as in Example 1. The pull-out strength of the OGFC-13 substrate was 2.68 MPa (after optimization), the contact angle was 42.5°, and the overall score was 84.8 points (Level II).

[0047] (4) Effect verification: Compared with the original formula, the pull-out strength of AC-13 substrate increased from 1.85MPa to 2.41MPa, the contact angle decreased from 52.3° to 44.7°, and the comprehensive score increased from 77.2 points (Level II) to 86.5 points (Level I). This indicates that increasing the amount of bio-based waterborne polyurethane emulsion and adding coupling agent can significantly improve the interfacial adhesion performance of waterborne traffic marking paint on different substrate surfaces.

[0048] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for evaluating the interfacial adhesion of water-based traffic marking paint, considering road surface texture and existing marking types, characterized in that, Includes the following steps: Step 1, Substrate preparation: Prepare asphalt specimens with different structural depths, and collect old hot-melt marking samples with different damage types; Step 2, Surface Characterization: The texture depth was determined by the sand-spreading method, the surface roughness was obtained by three-dimensional laser scanning, and the surface energy was determined by the contact angle method. Step 3, Wetting test: The static contact angle of the water-based coating on the surface of each substrate is measured using an optical contact angle meter to evaluate the wetting and spreading ability. Step 4, Adhesion strength test: After applying a 0.6 mm thick water-based coating and curing for 7 days, test the pull-out strength, shear strength, and pull-out strength retention rate after freeze-thaw cycles according to GB / T 5210. Step 5, Failure Mode Analysis: Observe the failure interface and calculate the area ratio of the failure region to determine whether it is adhesion failure, cohesive failure or mixed failure. Step 6, Multi-scale comprehensive evaluation: Establish a three-level indicator system of micro, meso, and macro levels, conduct weighted comprehensive scoring, and classify the adhesion level; The microscopic index system includes: surface energy matching degree and static contact angle; The detailed index system includes: surface roughness Ra and micromechanical interlocking coefficient C; The macro-indicator system includes: tensile strength, shear strength, and tensile strength retention rate after freeze-thaw cycles; The surface energy matching score is calculated as follows: A1 × weight W1 = 100 × [1 [(Δγ / 10)]×0.15, where Δγ is 1~10; The calculation of the static contact angle score is as follows: A2 × weight W2 = 100 × [1 [(θ / 180)]×0.10, where θ is 0~180; The surface roughness Ra score is calculated as follows: A3 × weight W3 = 100 × [1 (Ra0 Ra 2 ) / Ra0 2 ]×0.10, Ra reference value is 0~100; when Ra exceeds the reference value, it is calculated as Ra=Ra0; The specific calculation of the micromechanical locking coefficient C is as follows: A4 × weight W4 = C × 100 × 0.10, where C is 0~1; The specific calculation of the tensile strength σ is as follows: A5 × weight W5 = 0.2 × 100 × σ / 5, where σ is 0~5; The specific calculation of the shear strength τ is as follows: A6 × weight W6 = 100 × τ / 5 × 0.15, where τ is 0~5; The score for the retention rate of pull-out strength after freeze-thaw is calculated as follows: A7 × weight W7 = R × 0.20, R = (pull-out strength after freeze-thaw / initial pull-out strength) × 100%, where R is 0~100%. The formula for calculating the weighted comprehensive score S is: S = A1 × 0.15 + A2 × 0.10 + A3 × 0.10 + A4 × 0.10 + A5 × 0.20 + A6 × 0.15 + A7 × 0.20; When the weighted comprehensive score S≥85 points, at least 5 out of the 7 indicators must reach 85 points or above to prove that the coating has excellent overall performance on the substrate and belongs to the adhesion grade I (excellent). When 70 points ≤ weighted comprehensive score S < 85 points, all indicators are not lower than 60 points (passing line), and at least 3 items reach 80 points or above, it indicates that there are no significant shortcomings, the overall performance meets the standard, and the adhesion level is II (good). When 60 points ≤ weighted comprehensive score S < 70 points, and one or two indicators are below 60 points, it indicates that there are clear shortcomings that need to be improved in a targeted manner, and the adhesion level is Level III (Medium). When the weighted comprehensive score S < 60 points, and multiple indicators are below 60 points or any one indicator is below 40 points, it indicates that the substrate does not meet the conditions for engineering application and belongs to the adhesion level IV (poor).

2. The method for evaluating the interfacial adhesion of water-based traffic marking paint according to claim 1, characterized in that, The pretreatment of the asphalt specimens in step 1 is as follows: use high-pressure air to blow away surface dust and loose particles, wipe the surface with anhydrous ethanol if necessary and let it dry, and place it under standard conditions of temperature 23±2℃ and relative humidity 50±5% for more than 24 hours for later use. The pretreatment of old hot-melt marking samples in step 1 is as follows: use high-pressure air to blow away surface dust and loose particles. For samples with contamination, use a damp cloth to gently wipe away obvious dirt on the surface. Place the samples under standard conditions and let them stand for more than 24 hours before use.

3. The method for evaluating the interfacial adhesion of water-based traffic marking paint according to claim 1, characterized in that, The raw material for the asphalt specimens in step 1 is selected from at least one of AC-13, SMA-13, and OGFC-13, and the texture depth is 0.4~1.5mm; The old hot-melt marking samples in step 1 include five types of damage: wear and fading, cracking, peeling and flaking, blistering and bulging, and contamination and coverage. The freeze-thaw cycle conditions in step 4 are: freezing at -20℃ for 16 hours and then holding at 20℃ for 8 hours.

4. The method for evaluating the interfacial adhesion of water-based traffic marking paint according to claim 1, characterized in that, The failure mode analysis in step 5 is as follows: After the adhesion strength test is completed, retain and observe the two corresponding damaged surfaces. Without wiping or cleaning the residue on the damaged surfaces, take pictures in a way that is perpendicular to the damaged surfaces, and divide the failure area according to the location of the damage, the cross-sectional morphology and the material residue. When the damage mainly occurs at the interface between the water-based traffic marking coating and the asphalt mixture substrate or the existing old hot-melt marking substrate, and a large area of ​​the substrate surface is exposed, and there is no obvious tearing of the coating, old marking or asphalt mixture, it is judged as an adhesion failure. When the interface between the water-based coating and the substrate remains bonded, but the failure occurs inside the water-based coating, inside the old hot-melt marking, or inside the asphalt mixture, and corresponding material residue, tearing, aggregate pull-out, or mortar peeling can be observed on both damaged surfaces, it is judged as cohesive failure and noted as coating cohesive failure or substrate cohesive failure. When the same failure surface contains both an interface separation area where the substrate is exposed and an area where the coating or substrate is torn, it is determined to be a mixed failure.

5. The method for evaluating the interfacial adhesion of water-based traffic marking paint according to claim 1, characterized in that, Image analysis methods were used to calculate the area ratio of different failure areas. When the area of ​​interface adhesion failure accounts for no less than 80% of the effective damage area, it is judged as adhesion failure. When the sum of the areas of coating and substrate cohesive failure is no less than 80%, it is judged as cohesive failure. Other cases are judged as mixed failure. When the existing old hot melt markings are completely separated from the asphalt pavement, they are recorded separately as secondary interface failure of old hot melt markings-asphalt pavement.

Citation Information

Patent Citations

  • Marking paint and glass bead adhesion performance evaluation index and method

    CN112985973A

  • Marking paint adhesion testing method based on surface energy theory

    CN113804590A